Antarctic spore-forming microorganisms from deception island inhibit the growth of various bacterial strains - Sheau, Ting Yong; Chui, Peng-Teoh; Lavin, Paris Leonardo; Gonzales, Marcelo A.; Wong, Clemente Michael Vui Ling (Penerbit Universiti Kebangsaan Malaysia, 2024)
Antarctic microbes have evolved and adapted unique strategies to survive in the harsh polar environment. Apart from the ability to adapt to the low nutrient soil content and extremely dry and cold polar environment, a particular strategy used by Antarctic bacteria is the production of antimicrobial compounds that can eliminate rivals in the same niche, giving them a competitive edge over other microbes. In contrast, it is unclear whether spore-forming microbes possess similar antimicrobial properties as one of their survival strategies, especially those from the Antarctic volcanic Deception island in the West Antarctic. Hence, this study aims to isolate and characterize the spore-forming microbes in Deception Island, Antarctica, as well as to identify the ones that are equipped with the ability to inhibit other microorganisms. Microbes were isolated using various growth media and were segregated into clusters based on their random amplified polymorphic DNA (RAPD) fingerprints. A total of 90 strains were isolated and clustered into 30 groups at a similarity of 60%. Representative strains from each cluster were assayed for antimicrobial activities against 13 Gram-positive and Gram-negative test bacteria comprising human pathogens. Twenty-five strains exhibited the ability to inhibit at least one test bacterium. The four strains, A60, Im31, Im32 and Im33 that showed the strongest inhibitory activities were subjected to 16S or 18S rDNA sequencing and analysis to identify them. They were identified as Pseudogymnoascus, Bacillus, Leohumicola, and Talaromyces spp. The ability of the aforementioned microbes to thrive in harsh environments and compete with fierce competitors for scarce nutrients is probably due to their ability to produce antimicrobial compounds that target and kill their rivals.